A zinc metal poly-niobium-oxygen cluster-polyvinyl alcohol composite coating layer, a preparation method and application thereof
Patent Information
- Application Number
- CN202611138901.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]然而,锌金属负极在水系电解液中面临严峻的界面稳定性问题:锌沉积过程中易产生枝晶生长,同时伴随析氢、腐蚀等寄生副反应,导致电池库伦效率下降、循环寿命缩短
1、本发明合成了一种新型含镱铜的多铌氧簇,其具备高化学稳定性与富氧表面,能够有效打破PVA原有强氢键网络,通过氢键重构暴露大量亲锌氧位点,为锌离子提供快速传输通道,显著降低锌离子脱溶剂化能垒。
Smart Images

Figure CN122977442A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer gel composite material technology, specifically relating to a zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite material coating, its preparation method, and its application. Background Technology
[0002] With the continuous expansion of renewable energy grid connection, the development of low-cost, highly safe, and long-life grid-scale energy storage technologies has become a key research focus in the energy sector. Aqueous zinc metal batteries, with their low redox potential (-0.76 V) and high theoretical specific capacity (820 mAh g⁻¹) of zinc anode, are particularly promising. -1 With its advantages such as high natural abundance and intrinsic safety of aqueous electrolytes, it is considered an important candidate for the next generation of large-scale energy storage systems.
[0003] However, zinc metal anodes face severe interfacial stability issues in aqueous electrolytes: dendrite growth easily occurs during zinc deposition, accompanied by parasitic side reactions such as hydrogen evolution and corrosion, leading to decreased battery coulombic efficiency and shortened cycle life. Under actual operating conditions with high depth of discharge (DOD), the repeated deposition / stripping of zinc further exacerbates interfacial degradation, severely restricting the commercial application of zinc metal batteries.
[0004] Surface coating modification is one of the mainstream strategies for improving the interfacial stability of zinc anodes. Among them, polyvinyl alcohol (PVA) has attracted widespread attention due to its strong hydrophilicity, good film-forming properties, and low cost. However, pure PVA coatings have defects such as excessively strong intramolecular / intermolecular hydrogen bonding, low ionic conductivity, and slow interfacial charge transfer kinetics. Moreover, they are prone to structural damage during long-term cycling at high discharge depths, making it difficult to meet the requirements of deep-cycle operation.
[0005] Polyoxometalates (POMs) are a class of metal-oxygen cluster compounds formed by transition metal atoms and oxygen atoms, characterized by tunable structure, oxygen-rich surfaces, and strong electron mobility. Among them, polyniobium oxide clusters (PONbs) exhibit superior chemical inertness and structural stability compared to other POMs. Their surface oxygen atoms have higher electronegativity, possessing the potential to form strong hydrogen bonds with polymer hydroxyl groups. Introducing polyniobium oxide clusters into a PVA matrix is expected to break the original strong hydrogen bond network of PVA, reconstruct the hydrogen bond structure, and expose more zinc-loving active sites, while simultaneously improving the structural durability of the coating, thereby achieving stable cycling of the zinc anode at high depths of discharge. Currently, there are no reports on the use of polyniobium oxide cluster-modified PVA composite coatings for high depth-of-discharge zinc anode protection. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite material coating, its preparation method and application. This zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite material coating improves the ion transport dynamics and structural stability of the coating by reconstructing the PVA hydrogen bond network through multi-niobium oxygen clusters, thereby achieving a long cycle life of the zinc anode under high discharge depth conditions.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: A multi-niobium oxygen cluster for reconstructing a polyvinyl alcohol hydrogen bond network, wherein the chemical structural formula of the multi-niobium oxygen cluster for reconstructing a polyvinyl alcohol hydrogen bond network is K6H. 79 YbCu 24 Nb 56 O 208 ·78H2O; The crystal structure of the reconstructed polyvinyl alcohol hydrogen bond network multi-niobium oxygen cluster belongs to the triclinic crystal system, space group is 78H2O. The cell parameters are: a=21.6218(2)Å, b=26.7496(3)Å, c=32.9509(3)Å, α=91.5779(7)°, β=99.9092(7)°, γ=98.1524(9)°.
[0008] A zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite coating is provided. The zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite coating is formed by combining the multi-niobium oxygen clusters that reconstruct the hydrogen bond network of polyvinyl alcohol with polyvinyl alcohol as raw materials, and is cured on the surface of zinc metal substrate by in-situ coating. The multi-niobium oxygen clusters that reconstruct the hydrogen bond network of polyvinyl alcohol interact with the hydroxyl groups of the polyvinyl alcohol molecular chain through hydrogen bond interaction on their oxygen-rich surface, reconstructing the original hydrogen bond network of polyvinyl alcohol and exposing a large number of zinc-loving oxygen sites.
[0009] Preferably, the zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite material coating has an ultra-thin structure. When used as a zinc anode protective layer in zinc metal batteries, it can reduce the zinc ion desolvation energy barrier and accelerate the desolvation of Zn. 2+ The zinc migrates and induces preferential deposition along the (101) crystal plane, maintaining structural stability under high discharge depth charge-discharge conditions.
[0010] A method for preparing a zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite coating includes the following steps: S1, Synthetic precursor material Nb6 (K7HNb6O) 19 ·13H2O); S2. Mix Nb6, lithium tetraborate, isonicotinic acid, copper chloride dihydrate, ytterbium sulfate octahydrate, sodium carbonate and deionized water, and stir at room temperature until homogeneous to obtain a mixed reaction solution. S3. Place the mixed reaction solution in a hydrothermal reactor for hydrothermal reaction. After the reaction is completed, cool to room temperature and allow to stand to crystallize to obtain multi-niobium oxygen cluster crystals. S4. Dissolve the niobium-oxygen cluster crystals in ultrapure water, add polyvinyl alcohol, heat and stir until the solution is clear, and cool to room temperature to obtain the niobium-oxygen cluster-polyvinyl alcohol composite casting solution. S5. After grinding and cleaning the surface of the zinc sheet, apply the multi-niobium oxygen cluster-polyvinyl alcohol composite casting liquid to the surface of the zinc sheet, and dry it under vacuum heating to form a zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite material coating in situ.
[0011] Preferably, in step S3, the hydrothermal reaction temperature is 120°C, the reaction time is 3 days, and the static crystallization time is 3 days to obtain dark green niobium-oxygen cluster crystals.
[0012] Preferably, in step S4, the heating and stirring temperature is 80°C and the stirring time is 1 hour.
[0013] Preferably, in step S5, the zinc sheet surface polishing and cleaning process specifically involves: first polishing the zinc sheet with 2000-grit coarse sandpaper, wiping it clean with alcohol, then polishing it with 4000-grit fine sandpaper, and wiping it clean with alcohol again.
[0014] Preferably, in step S5, the vacuum heating drying temperature is 80°C and the drying time is 12 h.
[0015] An application of a multi-niobium oxygen cluster that reconstructs a polyvinyl alcohol hydrogen bond network is disclosed, wherein the multi-niobium oxygen cluster of the reconstructed polyvinyl alcohol hydrogen bond network is used to modify a polyvinyl alcohol coating for zinc anode interface protection in zinc metal batteries.
[0016] An application of a zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite material coating, wherein the zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite material coating is used as a zinc negative electrode protective layer in an aqueous zinc metal battery.
[0017] By adopting the above technical solution, the present invention has the following beneficial effects: 1. This invention synthesizes a novel ytterbium copper-containing multi-niobium oxygen cluster, which has high chemical stability and an oxygen-rich surface. It can effectively break the original strong hydrogen bond network of PVA, expose a large number of zinc-loving oxygen sites through hydrogen bond reconstruction, provide a fast transport channel for zinc ions, and significantly reduce the desolvation energy barrier of zinc ions.
[0018] 2. The zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite coating prepared by the present invention has an ultra-thin structure and is tightly bonded to the zinc substrate. It can uniformly control the zinc ion deposition behavior, induce zinc to preferentially deposit along the (101) crystal plane, and effectively suppress zinc dendrite growth and hydrogen evolution corrosion side reactions.
[0019] 3. The zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite material coating of the present invention exhibits excellent structural stability under high depth of discharge conditions: Zn / / Zn symmetric cells at 10 mAh·cm -2 Under high areal capacity (corresponding to depth of discharge DOD=85.5%), it can stably cycle for over 730 hours, far superior to bare zinc anodes (failure after 40 hours); the assembled Zn / / I2 full cell can cycle stably at 2 A·g -1 After 20,000 cycles at high current density, the capacity retention rate can still reach 90.1%, which is significantly better than that of pure zinc anode.
[0020] 4. The preparation process of this invention is simple and controllable, with low raw material costs, and is suitable for large-scale preparation. It provides a new technical path for the development of highly stable zinc anodes and also expands the application scenarios of polyoxometalate cluster materials in the field of energy storage. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of the crystal structure unit of the multi-niobium oxygen cluster of the present invention and a schematic diagram of the hydrogen bond regulation mechanism and preparation process of the composite coating; Figure 2 The crystal structure diagram and surface electrostatic potential distribution diagram of the multi-niobium oxygen cluster of the present invention are shown. Figure 3 The images show a comparison of experimental testing and single-crystal simulated powder diffraction of the multi-niobium oxygen clusters of this invention, as well as X-ray diffraction patterns of pure PVA coating and composite coating. Figure 4 Fourier transform infrared spectra of the multi-niobium oxygen cluster, pure PVA coating, and multi-niobium oxygen cluster-polyvinyl alcohol composite coating of the present invention; Figure 5 The images show the Raman spectra of the multi-niobium oxygen cluster, pure PVA coating, and multi-niobium oxygen cluster-polyvinyl alcohol composite coating of the present invention. Figure 6 This is the X-ray photoelectron spectrum of the multi-niobium oxygen cluster-polyvinyl alcohol composite coating of the present invention; Figure 7 This is a cross-sectional scanning electron microscope image of the multi-niobium oxygen cluster-polyvinyl alcohol composite material coating of the present invention; Figure 8 This is a comparison chart of the deep discharge long-cycle performance of the symmetrical battery with the composite coating modified zinc anode, the pure PVA modified zinc anode, and the bare zinc anode of the present invention. Figure 9 This is a comparison chart of the long-cycle performance of zinc-iodine full cells assembled with the composite-coated modified zinc anode and the bare zinc anode of the present invention. Detailed Implementation
[0022] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to examples. It should be understood that the specific examples described herein are merely illustrative and not intended to limit the invention.
[0023] See Figures 1 to 9 .
[0024] Example 1: K6H 79 YbCu 24 Nb 56 O 208 Preparation of ·78H2O (CuNb): S1, Synthetic precursor material Nb6 (K7HNb6O) 19 ·13H2O), the synthesis method is based on the method provided in the literature "Inorganic Chemistry" (Vol. 18, 1979, pp. 93-103).
[0025] S2. Add Nb6, lithium tetraborate, isonicotinic acid, copper chloride dihydrate, ytterbium sulfate octahydrate, sodium carbonate, and 8 mL of deionized water to a 25 mL polytetrafluoroethylene hydrothermal reactor liner. Stir magnetically at room temperature for 1 hour to ensure the reactants are mixed evenly.
[0026] S3. After sealing the hydrothermal reactor, place it in a forced-air drying oven and set the temperature to 120℃ for 3 days for hydrothermal reaction.
[0027] S4. After the reaction is complete, turn off the oven and allow the hydrothermal reactor to cool naturally to room temperature. Let it stand in place for 3 days. Dark green, regular crystals will precipitate at the bottom of the reactor, which are the multi-niobium oxygen clusters K6H that reconstruct the hydrogen bond network of polyvinyl alcohol. 79 YbCu 24 Nb 56 O 208 ·78H2O, abbreviated as CuNb.
[0028] Example 2: Preparation of zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite coating (PVA@CuNb) S1. Dissolve the CuNb crystals prepared in Example 1 in ultrapure water, add a certain amount of polyvinyl alcohol, heat the system to 80°C, stir magnetically for 1 hour until the solution is completely clear and transparent, stop heating, and cool naturally to room temperature to obtain a homogeneous multi-niobium oxygen cluster-polyvinyl alcohol composite casting solution.
[0029] S2. Zinc sheet pretreatment: First, use 2000-grit coarse sandpaper to polish the zinc sheet to remove the surface oxide layer, and wipe it clean with an alcohol swab; then use 4000-grit fine sandpaper for fine polishing, and wipe it clean again with an alcohol swab to obtain a zinc sheet substrate with uniform surface roughness.
[0030] S3. Apply the multi-niobium oxygen cluster-polyvinyl alcohol composite casting solution evenly to the surface of the treated zinc sheet using a scraper. Transfer the coated zinc sheet into a vacuum drying oven and vacuum dry at 80°C for 12 hours to form an in-situ zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite material coating, denoted as PVA@CuNb coating.
[0031] Comparative Example 1: Preparation of Pure PVA Coating Except for the absence of CuNb crystals, the other raw materials and process parameters are completely consistent with those in Example 2. A pure PVA coating is prepared on the surface of the zinc sheet, which is referred to as the PVA coating.
[0032] Experimental Example 1: Crystal Structure Determination Single-crystal samples with uniform size and regular shape prepared in Example 1 were selected under a microscope. A Bruker APEX II CCD single-crystal diffractometer was used with Mo-Kα rays (λ = 0.71073 Å) monochromated by a graphite monochromator as the incident light source, and single-crystal diffraction data were collected at 100 K. The crystal structure was resolved using the SHELXTL-97 program via a direct method. The non-hydrogen atom and anisotropic thermal parameters were refined using the full-matrix least squares method. Hydrogen atoms were obtained through theoretical hydrogenation. The main crystallographic parameters of the resulting compounds are shown in Table 1.
[0033] Table 1: Crystallographic parameters of multi-niobium oxygen clusters in the reconstructed polyvinyl alcohol hydrogen bond network Empirical formula <![CDATA[H 235 With 24 K6Nb 56 A 286 Yb]]> Formula weight 12056.30 Temperature / K 100.00(10) Crystal system triclinic Space group P-1 a / Å 21.6218(2) b / Å 26.7496(3) c / Å 32.9509(3) α / ° 91.5779(7) β / ° 99.9092(7) γ / ° 98.1524(9) <![CDATA[Volume / Å 3 ]]> 18557.6(3) Z 2 <![CDATA[ρ calc g / cm 3 ]]> 2.830 <![CDATA[μ / mm -1 ]]> 17.571 F(000) 15621.0 <![CDATA[Crystal size / mm 3 ]]> 0.1 × 0.1 × 0.1 2θ range for data collection / ° 4.196 to 154.61 Reflections collected 248599 Independent reflections 75711 Data / restraints / parameters 75711 / 13 / 2667 <![CDATA[GOF on F 2 ]]> 1.082 Final R indexes [I>=2σ (I)] <![CDATA[R1= 0.0813, wR2= 0.2519]]> Final R indexes [all data] <![CDATA[R1= 0.1090, wR2= 0.2804 <!-- 4 -->]]> <![CDATA[Largest diff. peak / hole / e Å -3 ]]> 2.88 / -4.26 Experimental Example 2: Phase and Structure Characterization 1. Powder X-ray diffraction test The CuNb crystals from Example 1 were thoroughly ground into powder, and then subjected to room-temperature powder X-ray diffraction testing. The results are as follows: Figure 3 As shown in section a, the positions of the diffraction peaks measured in the experiment are highly consistent with those obtained from the single-crystal data simulation, indicating that the prepared CuNb crystal is a pure phase without obvious impurities.
[0034] X-ray diffraction tests were performed on the PVA@CuNb coating of Example 2 and the PVA coating of Comparative Example 1. The results are as follows: Figure 3 As shown in section b, no obvious CuNb crystal characteristic peaks appeared in the composite coating, while the intensity of the characteristic carbon peak of PVA was weakened. This indicates that the addition of CuNb weakened the hydrogen bonding between PVA molecular chains, thus reducing the crystallinity of PVA.
[0035] 2. Infrared spectroscopy test Fourier transform infrared spectroscopy was performed on CuNb crystals, PVA coatings, and PVA@CuNb coatings. The results are as follows: Figure 4 As shown. CuNb crystals at 484 cm⁻¹ -1 527 cm -1and 661 cm -1 The characteristic peak at 831 cm⁻¹ is attributed to the vibrational absorption of the Nb-O bridging oxygen bond. -1 860cm -1 The characteristic peak at this location is attributed to the vibrational absorption of the Nb-O terminal oxygen bond. The presence and enhanced intensity of the aforementioned Nb-O characteristic peak can be observed in the composite coating, indicating a strong interaction between the CuNb clusters and the PVA matrix.
[0036] 3. Raman spectroscopy test Test results are as follows Figure 5 As shown. CuNb crystals are found in the 400-700 cm⁻¹ range. -1 The characteristic peak in the interval corresponds to the Nb-O bridging oxygen bond vibration, 913 cm⁻¹ -1 The characteristic peak at 855 cm⁻¹ corresponds to the oxygen bond vibration of the Nb-O terminal group. This peak can be observed in the PVA@CuNb composite coating. -1 1365 cm -1 and 1443 cm -1 The characteristic peaks at these locations are attributed to the vibrations of the CC, -CH2, and CO bonds, respectively; meanwhile, the presence of the Nb-O characteristic peaks further confirms the successful recombination and coupling between CuNb and PVA.
[0037] 4. X-ray photoelectron spectroscopy test Test results are as follows Figure 6 As shown. Figure 6 Characteristic peaks of Cu 2p and Nb 3d can be observed in parts a and b, proving that Cu and Nb elements have been successfully introduced into the composite coating; Figure 6 The C 1s and O 1s spectra in parts c and d show that the relative intensities of the CO and OH peaks in the composite coating change, indicating that the addition of CuNb weakens the intramolecular hydrogen bonds of PVA, exposing more free hydroxyl groups, which provides a structural basis for the increase of zinc-loving sites. At the same time, the characteristic peaks of Nb-O bonds appear, verifying the interaction between the two phases.
[0038] 5. Cross-sectional morphology characterization The cross-sectional morphology of the PVA@CuNb coating was observed using scanning electron microscopy, and the results are as follows: Figure 7 As shown, the coating thickness is approximately 150 nm, exhibiting a uniform and dense ultrathin structure that bonds tightly to the zinc foil substrate without any obvious gaps or defects.
[0039] Experimental Example 3: Electrochemical Performance Testing 1. Long-cycle performance test of zinc symmetric batteries Using the PVA@CuNb modified zinc sheet prepared in Example 2, the PVA modified zinc sheet in Comparative Example 1, and a bare zinc sheet as negative electrodes, CR2032 type button-type symmetrical batteries were assembled. The electrolyte was a 2 M ZnSO4 aqueous solution, and the electrolyte concentration was 1 mAh·cm⁻¹. -2 Current density, 10 mAh·cm -2 Under the condition of areal capacity, constant current charge-discharge cycle test was performed, and the corresponding zinc anode discharge depth was about 85.5%.
[0040] Test results are as follows Figure 8 As shown, the bare zinc symmetric cell experienced a voltage surge and failed after only 40 hours of cycling; the pure PVA-modified zinc anode showed improved cycle stability, but voltage fluctuations still occurred within a short period; while the PVA@CuNb-modified zinc anode could cycle stably for more than 730 hours, and the voltage polarization remained at a low level throughout, indicating that the composite coating significantly improved the interfacial stability of the zinc anode at high discharge depths.
[0041] 2. Long-cycle performance test of zinc-iodine full cells Zn / / I₂ full cells were assembled using PVA@CuNb modified zinc sheets and bare zinc sheets as negative electrodes, respectively, and matched with iodine-based positive electrodes. The results were obtained at 2 A·g -1 Long-cycle performance tests were conducted at current densities.
[0042] Test results are as follows Figure 9 As shown, the capacity of a full cell assembled with a bare zinc anode decays rapidly during cycling, with a capacity retention of only 72.3% after cycling; while the full cell assembled with a PVA@CuNb modified zinc anode still retains a capacity retention of 90.1% after 20,000 cycles, demonstrating excellent long-cycle durability and proving that the composite coating has excellent interface protection effect in actual battery systems.
[0043] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A multi-niobium oxygen cluster for reconstructing a polyvinyl alcohol hydrogen bond network, characterized in that: The chemical structural formula of the reconstructed polyvinyl alcohol hydrogen bond network multi-niobium oxygen cluster is K6H. 79 YbCu 24 Nb 56 O 208 ·78H2O; The crystal structure of the reconstructed polyvinyl alcohol hydrogen bond network multi-niobium oxygen cluster belongs to the triclinic crystal system, space group is 78H2O. The cell parameters are: a=21.6218(2)Å, b=26.7496(3)Å, c=32.9509(3)Å, α=91.5779(7)°, β=99.9092(7)°, γ=98.1524(9)°.
2. A zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite material coating, characterized in that: The zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite coating is formed by combining the multi-niobium oxygen clusters reconstructing the polyvinyl alcohol hydrogen bond network as described in claim 1 with polyvinyl alcohol as raw material, and is cured on the surface of the zinc metal substrate by in-situ coating; the multi-niobium oxygen clusters reconstructing the polyvinyl alcohol hydrogen bond network interact with the hydroxyl groups of the polyvinyl alcohol molecular chain through hydrogen bond interaction on their oxygen-rich surface, reconstructing the original hydrogen bond network of polyvinyl alcohol and exposing a large number of zinc-loving oxygen sites.
3. The zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite material coating as described in claim 2, characterized in that: The zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite material coating has an ultra-thin structure. When used as a zinc anode protective layer in zinc metal batteries, it can reduce the zinc ion desolvation energy barrier and accelerate Zn... 2+ The zinc migrates and induces preferential deposition along the (101) crystal plane, maintaining structural stability under high discharge depth charge-discharge conditions.
4. A method for preparing a zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite material coating as described in claim 2 or 3, characterized in that, Includes the following steps: S1, Synthetic precursor material Nb6 (K7HNb6O) 19 ·13H2O); S2. Mix Nb6, lithium tetraborate, isonicotinic acid, copper chloride dihydrate, ytterbium sulfate octahydrate, sodium carbonate and deionized water, and stir at room temperature until homogeneous to obtain a mixed reaction solution. S3. Place the mixed reaction solution in a hydrothermal reactor for hydrothermal reaction. After the reaction is completed, cool to room temperature and allow to stand to crystallize to obtain multi-niobium oxygen cluster crystals. S4. Dissolve the niobium-oxygen cluster crystals in ultrapure water, add polyvinyl alcohol, heat and stir until the solution is clear, and cool to room temperature to obtain the niobium-oxygen cluster-polyvinyl alcohol composite casting solution. S5. After grinding and cleaning the surface of the zinc sheet, apply the multi-niobium oxygen cluster-polyvinyl alcohol composite casting liquid to the surface of the zinc sheet, and dry it under vacuum heating to form a zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite material coating in situ.
5. The method for preparing the zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite material coating as described in claim 4, characterized in that: In step S3, the hydrothermal reaction temperature is 120℃ and the reaction time is 3 days; the static crystallization time is 3 days to obtain dark green niobium-oxygen cluster crystals.
6. The method for preparing the zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite material coating as described in claim 4, characterized in that: In step S4, the heating and stirring temperature is 80°C, and the stirring time is 1 hour.
7. The method for preparing the zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite material coating as described in claim 4, characterized in that: In step S5, the zinc sheet surface polishing and cleaning process is as follows: first, polish the zinc sheet with 2000-grit coarse sandpaper, wipe it clean with alcohol, then polish it with 4000-grit fine sandpaper, and wipe it clean with alcohol again.
8. The method for preparing the zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite material coating as described in claim 4, characterized in that: In step S5, the vacuum heating drying temperature is 80°C and the drying time is 12 h.
9. An application of the multi-niobium oxygen cluster of the reconstructed polyvinyl alcohol hydrogen bond network as described in claim 1, characterized in that: The reconstructed polyvinyl alcohol hydrogen bond network with niobium-oxygen clusters is used to modify polyvinyl alcohol coatings for zinc anode interface protection in zinc metal batteries.
10. The application of a zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite material coating as described in claim 2 or 3, characterized in that: The zinc metal multi-niobium oxygen cluster-polyvinyl alcohol composite material coating is used as a zinc negative electrode protective layer in aqueous zinc metal batteries.